Pengembangan Media Animasi Kartun berbasis Model 4D untuk Meningkatkan Pemahaman Algoritma Pengurutan - Antula, Nur Savira; Bouty, Abd. Aziz; Suhada, Sitti; Amali, Lanto Ningrayati; Pakaja, Jemmy; Bau, Rahmat Taufik R. L. (Universitas Negeri Gorontalo, 2024)
Students often face difficulties in understanding sorting algorithm material due to its abstract nature and the lack of engaging and interactive learning media. This study aims to develop cartoon animation-based learning media as an innovative solution to improve students' understanding of sorting algorithm material. The research method used was Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The developed media was evaluated by subject matter experts, media experts, and students to assess its feasibility, practicality, and effectiveness. The results showed that the media is highly feasible, with a feasibility score of 99% from subject matter experts, 85% from media experts, and a practicality response of 96% from students. Additionally, the media effectively enhanced students' understanding, with an average learning outcome improvement of 75%. This cartoon animation-based media not only facilitates students in comprehending complex algorithm concepts but also provides a significant contribution to the development of technology-based learning. Kesulitan siswa dalam memahami materi algoritma pengurutan sering kali disebabkan oleh sifatnya yang abstrak dan minimnya media pembelajaran yang menarik dan interaktif. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis animasi kartun sebagai solusi inovatif untuk meningkatkan pemahaman siswa terhadap materi algoritma pengurutan. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model 4D (Define, Design, Develop, Disseminate). Media yang dikembangkan dievaluasi oleh ahli materi, ahli media, dan siswa untuk menilai kelayakan, kepraktisan, dan efektivitasnya. Hasil penelitian menunjukkan bahwa media ini sangat layak digunakan, dengan skor kelayakan 99% dari ahli materi, 85% dari ahli media, dan respons kepraktisan sebesar 96% dari siswa. Selain itu, media ini terbukti efektif dalam meningkatkan pemahaman siswa dengan rata-rata peningkatan hasil belajar sebesar 75%. Media animasi kartun ini tidak hanya mempermudah siswa dalam memahami konsep algoritma yang kompleks, tetapi juga memberikan kontribusi penting dalam pengembangan pembelajaran berbasis teknologi.